2018
DOI: 10.30877/ijmh.5.3.2018.296-300
|View full text |Cite
|
Sign up to set email alerts
|

A Study to assess Depression levels in MBBS Students

Abstract: Background and Objectives: Medical education can be quite stressful and studies all over the world have consistently shown a high prevalence of depression in medical students. In India, the prevalence of depression was around 39%. It was observed that the prevalence of provisionally diagnosed depressive disorder and major depressive disorder in medical students was 21.5% and 7.6%, respectively. Our plan is to assess the depression level in the students and according treatment will be given Methods: The study d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…For example, in a study of Chinese medical students, the mean PHQ-9 score was 6.02, with 13.5% of respondents reporting scores that reflect MDD (Sobowale et al, 2014). Similarly, a large study of South Korean medical students found that 13.7% of students scored in the moderate to severe range (Yoon et al, 2014) and rates of MDD among medical students in India were found to be over 30% (Patil et al, 2018). A study of medical students in Cameroon found that 30.6% scored in the moderate to severe range (Ngasa et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a study of Chinese medical students, the mean PHQ-9 score was 6.02, with 13.5% of respondents reporting scores that reflect MDD (Sobowale et al, 2014). Similarly, a large study of South Korean medical students found that 13.7% of students scored in the moderate to severe range (Yoon et al, 2014) and rates of MDD among medical students in India were found to be over 30% (Patil et al, 2018). A study of medical students in Cameroon found that 30.6% scored in the moderate to severe range (Ngasa et al, 2017).…”
Section: Discussionmentioning
confidence: 99%